Simplifying
9x^{4}y^{5}(-5x^{3}y^{3} + -3y^{3}) = 0
(-5x^{3}y^{3} * 9x^{4}y^{5} + -3y^{3} * 9x^{4}y^{5}) = 0
Reorder the terms:
(-27x^{4}y^{8} + -45x^{7}y^{8}) = 0
(-27x^{4}y^{8} + -45x^{7}y^{8}) = 0
Solving
-27x^{4}y^{8} + -45x^{7}y^{8} = 0
Solving for variable 'x'.
Factor out the Greatest Common Factor (GCF), '-9x^{4}y^{8}'.
-9x^{4}y^{8}(3 + 5x^{3}) = 0
Ignore the factor -9.
#### Subproblem 1

Set the factor 'x^{4}y^{8}' equal to zero and attempt to solve:
Simplifying
x^{4}y^{8} = 0
Solving
x^{4}y^{8} = 0
Move all terms containing x to the left, all other terms to the right.
Simplifying
x^{4}y^{8} = 0
The solution to this equation could not be determined.
This subproblem is being ignored because a solution could not be determined.
#### Subproblem 2

Set the factor '(3 + 5x^{3})' equal to zero and attempt to solve:
Simplifying
3 + 5x^{3} = 0
Solving
3 + 5x^{3} = 0
Move all terms containing x to the left, all other terms to the right.
Add '-3' to each side of the equation.
3 + -3 + 5x^{3} = 0 + -3
Combine like terms: 3 + -3 = 0
0 + 5x^{3} = 0 + -3
5x^{3} = 0 + -3
Combine like terms: 0 + -3 = -3
5x^{3} = -3
Divide each side by '5'.
x^{3} = -0.6
Simplifying
x^{3} = -0.6
The solution to this equation could not be determined.
This subproblem is being ignored because a solution could not be determined.
The solution to this equation could not be determined.